Development of a Practical Tool for Renewable Energy Materials in P5 Activities Based on Secang Extract as a Natural Dye Sensitizer in the DSSC Circuit - Ridho Sastriwijaya; Dini Hadiarti; Raudhatul Fadhillah (Postgraduate, University of Mataram, 2025)
In this study, a DSSC practice tool based on sappanwood (Caesalpinia sappan L.) extract as a natural dye sensitizer was developed to support renewable energy learning at the senior high school level. This research is categorized as development research, aiming to produce a renewable energy practice tool that is valid and practical. The method used in this study was Research and Development (R&D), adapted from the Thiagarajan 3D model. The results showed that the practice tool based on sappanwood extract as a natural dye sensitizer in the DSSC circuit was declared highly feasible, with an assessment score of 85% from media experts and 86% from material experts.The product trials revealed that the small-group trial achieved a feasibility score of 83%, while the large-group trial reached 86%. Both results were categorized as “highly feasible.” These findings indicate that the DSSC practice tool based on sappanwood extract as a natural dye sensitizer is valid and practical for use in the learning process